Assessment of Land Surface Changes in the Vicinity of Underground Gas Storage Using Multispectral Remote Sensing - A. Kaczmarek; J. Blachowski (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Geological formations are used worldwide for storage of energy sources and carriers such as natural gas and hydrogen, but also carbon dioxide. Caverns in rock salt are a specific type as due to the properties of salt, they are particularly suitable for long term safe and stable storage of various materials. However, the operation interacts with the environment in several ways, with ground movements being the most observed. The purpose of this study was to analyse land cover changes in the vicinity of underground gas storage based on a case study area of Kosakowo, Poland. The region is mainly agricultural with a neglected drainage system, located close to the sea, at low altitude, making it prone to waterlogging. The condition and changes in land surface, with vegetation and surface water monitoring in particular, were analysed using spectral indices derived from the ESA Copernicus Sentinel-2 data. In the study, it was tested and validated whether and if open multispectral satellite data in connection with spatial statistics can be effectively used for monitoring land cover changes in such regions.